5-(Fluorodinitromethyl)-2H-tetrazole and its tetrazolates – Preparation and Characterization of New High Energy Compounds1. Issue 22 (14th June 2015) - Haiges, Ralf; Christe, Karl O.
<x xml:space="preserve">Abstract</x> 5-(Fluorodinitromethyl)-2H-tetrazole (HFDNTz) has been prepared by the cycloaddition reaction of HN3 with F(NO2)2CCN, which in turn was prepared by aqueous fluorination of sodium dinitrocyanomethanide.